A STUDY OF LINGUISTIC FEATURESOF PROVERBS EXPRESSING SUPERSTITION IN ENGLISH AND VIETNAMESE - Trần Thị Tuyết Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Due to own extraordinary features, proverb is regarded as a special field of any languages, therefore attracts a lot of attention to its uniqueness. Proverbs expressing superstition are no exception. This thesis is to study syntactic and semantic features of proverbs expressing superstition in English and Vietnamese with the descriptive and contrastive method. Both qualitative and quantitative analysis is conducted basing on the investigation of 300 proverbs expressing superstition in English and Vietnamese. The findings show that these proverbs expressing superstition have remarkable syntactic and semantic features and that there are some similarities and differences between them. Some implications for teaching and learning English and Vietnamese as a foreign language could finally be put forward in the thesis.